The Effectiveness of E-Learning Based Islamic Religious Education on Students' Islamic Understanding at SMP Muhammadiyah 5 Kerjo - Yusuf Mahendra; Chusniatun Chusniatun; Hafidz Hafidz (Universitas Muhammadiyah Surakarta, 2025)
Islamic Religious Education plays a strategic role in shaping students’ Islamic understanding. However, its implementation in schools is still largely dominated by conventional learning approaches that are less responsive to technological advancements and the characteristics of students in the digital era. This study aims to analyze the effectiveness of e-learning based Islamic Religious Education in improving students’ Islamic understanding. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The research was conducted at SMP Muhammadiyah 5 Kerjo, involving an experimental group that received e-learning based Islamic Religious Education instruction and a control group that received conventional Islamic Religious Education instruction. Data were collected through tests measuring students' Islamic understanding, while data analysis included descriptive and inferential statistical analyses, preceded by prerequisite tests and difference tests to determine the effectiveness of the treatment. The findings indicate that e-learning based Islamic Religious Education has a positive effect and is more effective in enhancing students’ Islamic understanding compared to conventional Islamic Religious Education instruction. The study concludes that e-learning based Islamic Religious Education is feasible to be implemented as an alternative instructional strategy in schools. The contribution of this study lies in strengthening empirical evidence regarding the effectiveness of e-learning based Islamic Religious Education and providing practical implications for teachers and schools in developing Islamic education that is adaptive to technological advancements.